Composition, seasonal and interannual dynamics of zooplankton in Peter the Great Bay (Japan Sea) - Natalia T. Dolganova; Victoria V. Nadtochy (Известия ТИНРО)
Species structure, abundance and biomass of zooplankton, its seasonal and interannual dynamics are considered on the data of plankton surveys conducted in Peter the Great Bay in 2002-2013. All zooplankton species dwelling in the northwestern Japan Sea are presented in the fauna of Peter the Great Bay. Small-sized fraction of zooplankton prevais everywhere in the Bay (> 80 % of total number of animals). The zooplankton concentration in spring-summer (1280 mg/m3 on average) is in 1.4 times higher than in fall-winter. Both abundance and biomass of zooplankton are higher in the neritic zone in all seasons: the mean annual values are 53.17 thousand ind./m3 and 1370 mg/m3, respectively. The highest values are observed in the secondary bays, as the Amur Bay and Ussuri Bay (1455 mg/m3 on average). The Amur Bay is distinguished by high abundance of meroplankton, as well, in particular in its northern shallow area; its annual mean value is 3.65 thousand ind./m3 (twice higher than in the Ussuri Bay), the peaks are observed in summer and autumn. Abundance and biomass of zooplankton decrease gradually with the distance from the coast to the minimum values in the deep-water zone: 3.43 thousand ind./m3 and 485 mg/m3 on average, respectively. The total stock of zooplankton in Peter the Great Bay is estimated as 428. 103 t in spring and 636. 103 t in summer. Both seasonal and interannual dynamics of zooplankton abundance are more significant in the coastal areas, as the Amur and Ussuri Bays, where the changes are either similar (as in 2008, 2010-2013) or not (as in 2007, 2009). For example, low abundance of P. newmani but extremally high abundance of warm-water copepods (10 times higher than usually) and Bivalvia larvae were recorded in both bays in 2013. Fluctuations of large-sized oceanic species abundance have no essential impact on the total biomass of zooplankton in Peter the Great Bay. In general, the zooplankton abundance increased in 1.2-2.5 times during the decade, up to the maximum in 2010-2012, mainly because of Pseudocalanus newmani stock growth, but this species abundance decreased sharply in 2013 that caused 20 % reduction of the total zooplankton biomass.